Use of Botulinum Toxin for Limb Immobilization for Rehabilitation in Rats with Experimental Stroke - Hongxia Zhang; Jialing Liu; Deborah Bingham; Adrienne Orr; Masahito Kawabori; Jong Youl Kim; Zhen Zheng; Tina I. Lam; Stephen M. Massa; Raymond A. Swanson; Midori A. Yenari (Biomolecules, 2023)
Motor rehabilitation strategies after unilateral stroke suggest that the immobilization of the healthy, unimpaired limb can promote the functional recovery of a paretic limb. In rodents, this has been modeled using casts, harnesses, and other means of restricting the use of the non-paretic forelimb in models of experimental stroke. Here, we evaluated an alternative approach, using botulinum toxin injections to limit the function of the non-paretic forelimb. Adult male rats were subjected to permanent ligation of the left distal middle cerebral artery, resulting in right forelimb paresis. The rats were then subjected to: (1) no treatment; (2) botulinum toxin injections 1 day post stroke; or (3) cast placement 5 days post stroke. Casts were removed after 5 weeks, while the botulinum toxin injection effectively immobilized subjects for approximately the same duration. Rats with bilateral forelimb impairment due to the stroke plus casting or botulinum injections were still able to feed and groom normally. Both immobilization groups showed modest recovery following the stroke compared to those that did not receive immobilization, but the casting approach led to unacceptable levels of animal stress. The botulinum toxin approach to limb immobilization had both advantages and disadvantages over traditional physical limb immobilization. The major advantage was that it was far less stress-inducing to the subject animals and appeared to be well tolerated. A disadvantage was that the paresis took roughly 10 weeks to fully resolve, and any degree of residual paresis could confound the interpretation of the behavioral assessments.